Crimes of Genocide in the Viewpoint of International Criminal Law - Dewa Gede Sudika Mangku; Ni Putu Ray Yuliartini; Ayu Nadya Gayatri; Seguito Monteiro (IJCLS (Indonesian Journal of Criminal Law Studies), 2022)
Genocide is one of the crimes that are included in gross violations of human hights where this crime is related to ethnic cleansing which is also included in crimes against various political groups because it is difficult to identify which causes an international problem in a country. The crime of genocide in international criminal law is an extraordinary crime and is a prohibited act which was later included in the 1948 Genocide Convention, the statutes of the International Criminal Tribunals for the Former Yugoslavia (ICTY), the statutes of the International Criminal Tribunals for the Rwanda (ICTR) and the 1998 Rome statute. This study is intended to analyze the crime of genocide in the perspective of international law. This study found that the analysis and discourse of genocide in intersected with human rights theory and state responsibility. Genocide also highlighted as international crimes that are included in 4 (four) international crimes, namely genocide, crimes against humanity, war crimes, and crimes of aggression. In the Indonesian National Law Regulation, the Law of the Republic of Indonesia Number 26 of 2000 concerning the Human Rights Court in Article 7 states, the Crime of Genocide is a grave violation of human rights.